Community empowerment model of coastal border based on ecotourism - Toto Sugito; Adhi Iman Sulaiman; Ahmad Sabiq; Muslih Faozanudin; Bambang Kuncoro (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Development in coastal areas is an essential priority for overcoming social and economic gaps and conflicts through empowerment programs. The purpose of this research is to create a model of ecotourism-based coastal community empowerment. This study uses the Participatory Rural Appraisal (PRA) qualitative research method by collecting data through in-depth interviews, observation, documentation analysis, Focus Group Discussion (DKT) and Participatory Decision Making (PDM). Research locations in the border area of West Kalimantan are Sebubus Village and Temajuk Village, Paloh District, Sambas Regency. The informants of this study were 35 people consisting of empowerment activists, community leaders, village government, business groups, academics, and tourists. Research data were analysed using a SWOT analysis. The results showed 1) To develop the potential of mangrove forest ecotourism and processing of food from mangrove fruit, sea turtle breeding, and coastal inheritance, participatory empowerment programs are needed; 2) Youth activists become activists of empowering ecotourism with community leaders needing support and cooperation with village and regional governments, as well as the private sector; and 3) The need to improve road infrastructure, electricity and telecommunications signals, especially in Temajuk Village so as not to cause social and economic dependence and jealousy with the Malaysian border area.